Teknik dan Taktik Penimbunan Bahan Bakar Minyak (Studi Kasus Pada Direktorat Krimsus Polda Maluku) - Reyhard Jonathan Ilely; Deassy Jacomina Anthoneta Hehanussa; Lionie Lokollo (Faculty of Law Pattimura University, 2021)
Introduction: Oil and gas are natural resources that are controlled by the state and have an important role for the national economy. Therefore, it is necessary to manage them as much as possible.Purposes of the Research: The purpose of this research is to study, analyze and explain the techniques and tactics of stockpiling fuel oil.Methods of the Research: The method used is normative juridical with a statutory approach, a conceptual approach and a case approach. Sources of legal materials used are primary and secondary. The collection technique is through literature study and analyzed through descriptive method using qualitative methods.Results of the Research: The results showed that the techniques and tactics in handling fuel stockpiles were interrogation techniques and tactics, case title techniques and tactics and investigative management techniques and tactics